Numerical solution for the problem on spread of pollution in underground water in Hanoi - Anh, Nguyen Nam; Hien, Ha Ngoc; Trung, Mai Dinh (Vietnam Journal of Mechanics, 1995)
In this paper a mathematical model for problem of pollution transport in groundwater aquifer in Hanoi is presented. To obtain numerical solution of the problem a method of finite difference was applied. The result for practical case when pollution is contaminated only from hydrogeological windows in product layer has been obtained.